Evaluation of persistent organochlorine pesticides and polychlorinated biphenyls in Umgeni River bank soil, KwaZulu- Natal, South Africa - Gakuba, Emmanuel; Moodley, Brenda; Ndungu, Patrick; Birungi, Grace (Water SA, 2019)
This study investigated the presence and distribution of organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) in soil collected along the banks of the Umgeni River, one of the largest rivers in the province of KwaZulu-Natal, South Africa. _e analysis was performed using gas chromatography-mass spectrometry (GC-MS). _e results showed that the levels of OCPs ranged from 3.58±0.09 ng/g for hexachlorobenzene (HCB) to 82.65±2.82 ng/g for HCH, with an individual mean concentration of 24.33±2.00 ng/g dry weight (dw). _e levels of PCBs ranged from 10.46 ng/g for PCB105 to 89.46 ng/g for PCB180, with an average PCB value of 25.47±1.26 ng/g, dw. _e highest levels of OCPs and PCBs were found at Northern Wastewater Treatment Plant (mean OCP: 32.39±3.97 ng/g and PCB: 67.87±1.67 ng/g). _e two most abundant contaminants in the river were endrin and PCB180.
Keywords: Umgeni River; bank soil; OCPs; PCBs; gas chromatography mass spectrometry